Apparent digestibility coefficients of banana peel, cassava peel, cocoa husk, copra waste, and sugarcane bagasse in the GIFT strain of Nile tilapia (Oreochromis niloticus). Issue 3 (3rd July 2022) - Yossa, Rodrigue; Ahmad Fatan, Nurulhuda; Kumari, Jana; Schrama, Johan W.
ABSTRACT: This study was conducted to estimate the apparent digestibility coefficients (ADC) of the nutrients and energy contained in banana peel, cassava peel, cocoa husk, copra waste, and sugarcane bagasse in GIFT Nile tilapia (initial body weight 22.38 ± 0.33 g). A reference diet was formulated to satisfy the nutrient requirement of the fish. Five test diets were formulated to contain 70% of the reference diet and 30% of each test ingredient. The experiment lasted 42 days. The ADCs of dry matter (DM), crude lipid (CL), ash, crude fiber (CF), total carbohydrate (TC), and gross energy (GE) were 16.19%, 6.56%, 11.40%, 38.98% and 15.68% for banana peel; the ADCs of DM, crude protein (CP), CL, ash, CF, TC, and GE were 69.11%, 31.61%, 61.07%, 68.88%, 73.14%, 71.24%, and 69.00% for cassava peel; the ADCs of DM, ash, CF, TC, and GE were 10.56%, 0.84%, 28.70%, 2.82%, and 8.459.69% for cocoa husk; the ADCs of DM, CP, CL, ash, CF, TC, and GE were 63.08%, 20.14%, 66.60%, 32.53%, 69.70%, 66.21%, and 64.06% for copra waste; and the ADCs of DM, CF, TC, and GE were 15.22%, 36.71%, 34.34%, and 15.55% for sugarcane bagasse in tilapia respectively. This experiment generated basic information for the use of these ingredients in diet formulation for tilapia. However, considering the relatively low ADCs of nutrients observed in the present experiment, further processing could be an interesting avenue in improving the nutritional value and digestibility of these ingredients.